The Effect of Childhood Adversities and Protective Factors on the Development of Child-Psychiatric Disorders and Their Treatment - Bachler, Egon; Frühmann, Alexander; Bachler, Herbert; Aas, Benjamin; Nickel, Marius; Schiepek, Guenter Karl (Frontiers in Psychology, 2018)
CONTEXT: Families with high rates of childhood adversities (CAs) (Multi-problem-families-MPF) have an increasing importance in public health-policy. OBJECTIVE: The present study addresses the relationship between risk- and protective factors and the severity and treatment-outcome of mental disorders. SETTING: Family-therapeutic home-based treatment for MPF. We examined a clinical sample (N = 1031) of children between the age of 4 to 17, and a non-clinical sample of 148 children. We hypothesized that of all children of the clinical group have a predominance of risk factors and a higher number of psychopathological symptoms. Furthermore, we hypothesized that children with a predominance of protective factors benefit stronger from psychotherapy. MAIN RESULTS: In the clinical sample, most children met the criteria of a psychopathological diagnosis (95.7%, as compared to 21.6% in the non-clinical sample) and showed significant higher rates of childhood adversities and significant less protective factors as compared to the non-clinical sample. The clinical group showed a significant reduction of psychopathological symptoms and benefitted equally well from treatment. The number of risk factors was a significant predictor for a child from the non-clinical sample to meet the criteria of a psychopathological diagnosis, while the number of protective factors significantly predicted the absence thereof. CONCLUSION: Children and adolescents with high scores of CAs show significant associations with child psychiatric symptoms (d = 0.35; including all ICD-diagnosis such as e.g. Asperger-Syndrome, ADHD etc. with a higher rate of genetic etiology). Early life stressors however do not trigger an irreversible fate, as psychotherapy with young people with high numbers of risk factors does help to reduce psychopathological symptoms significantly (range of 5 outcome parameters: d = 0.31 – 0.72).